Healthcare workers' perceptions of the duty to work during an influenza pandemic. Issue 1 (21st December 2009) - Damery, S; Draper, H; Wilson, S; Greenfield, S; Ives, J; Parry, J; Petts, J; Sorell, T
Abstract : Healthcare workers (HCWs) are often assumed to have a duty to work, even if faced with personal risk. This is particularly so for professionals (doctors and nurses). However, the health service also depends on non-professionals, such as porters, cooks and cleaners. The duty to work is currently under scrutiny because of the ongoing challenge of responding to pandemic influenza, where an effective response depends on most uninfected HCWs continuing to work, despite personal risk. This paper reports findings of a survey of HCWs (n = 1032) conducted across three National Health Service trusts in the West Midlands, UK, to establish whether HCWs' likelihood of working during a pandemic is associated with views about the duty to work. The sense that HCWs felt that they had a duty to work despite personal risk emerged strongly regardless of professional status. Besides a strong sense that everyone should pull together, all kinds of HCWs recognised a duty to work even in difficult circumstances, which correlated strongly with their stated likelihood of working. This suggests that HCWs' decisions about whether or not they are prepared to work during a pandemic are closely linked to their sense of duty. However, respondents' sense of the duty to work may conflict with their sense of duty to family, as well as other factors such as a perceived lack of reciprocity from their employers. Interestingly, nearly 25% of doctors did not consider that they had a duty to work where doing so would pose risks to themselves or their families.